The Impact of Live Streaming, Free Shipping Vouchers, and Promotions on Purchase Decisions in TikTok Shop - Parwati, Dedin; Nurchayati; Hasyim; Mardiyono, Aris (LifeSciFi, 2025)
In the digital era, social media has played a crucial role in influencing consumer behavior, particularly through the emergence of online shopping platforms such as TikTok Shop. The accessibility of online shopping has expanded to various segments of society, making it essential to understand the factors that influence consumer purchasing decisions on this platform. This study examines the impact of live streaming, free shipping vouchers, and promotions on consumer purchase decisions within the TikTok Shop ecosystem. The research was conducted among undergraduate students from the Faculty of Economics and Business at UNTAG Semarang who actively use the live streaming feature on TikTok Shop. A total of 77 respondents, aged between 20 and 25 years, were selected as the study sample. The data were analyzed using multiple linear regression analysis to determine the significance of each factor. The findings indicate that live streaming, free shipping vouchers, and promotions each significantly and positively impact consumer purchase decisions. The significance test results demonstrate that increased engagement with live streaming directly enhances consumer trust and understanding of the products, leading to higher purchase intentions. Additionally, attractive promotions and free shipping vouchers serve as strong incentives, encouraging consumers to complete transactions. The implications of this study highlight the importance for businesses to leverage live streaming, offer free shipping vouchers, and implement effective promotional strategies. These efforts can enhance purchase decisions among undergraduate students at UNTAG Semarang and foster greater consumer satisfaction and loyalty towards products sold on TikTok Shop.